KRITIK SENI EKSPRESIONISME PADA KARYA LUKIS AGAPETUS â€œBAIK BOEROEK TANAH AIRKOE JOEGAâ€ - Rahma, Elvira Putri Syuhra Nazilatur; Astawan, I Kadek Yudi (Kusa Lawa, 2023)
Expressionism Art Criticism on Agapetusâ€™ Painting â€œBaik Boeroek Tanah Airkoe Joegaâ€. Agapetus is an artist withÂ  aÂ  surrealist visual concept whose focus is on animals as the subject matter. Agapetus talks a lot about the social condition of society through the representation of animals. This research wants to explore the meaning contained in the work "Baik Boeroek Tanah Airkoe Juga" through an art criticism approach. This research was conducted to describe, interpret, and evaluate works from the perspective of Expressionism criticism. This research wants to analyze the message and meaning that Agapetus wants to convey. Themes, form visualizations, and similar works become references in analyzing this work. Data is collected through various sources, such as articles, books, and online media documentaries. The research results are presented in the form of a descriptive narrative.